Juvenile Kearns-Sayre syndrome initially misdiagnosed as a psychosomatic disorder. Issue 1 (January 1994) - Nørby, S; Lestienne, P; Nelson, I; Nielsen, I M; Schmalbruch, H; Sjö, O; Warburg, M
Abstract : We have investigated a 15 year old girl with progressive external ophthalmoplegia, including bilateral ptosis and retinal rod and cone cell dysfunction with atypical retinal pigmentation, complicated by cerebellar ataxia, partial cardiac conduction block, and diabetes mellitus. In infancy she had a severe crisis of bone marrow depression, and as a child she suffered from hypersensitivity to light, increasing fatigue, and vertigo, signs that were initially though to be psychosomatic. Histological examination showed mitochondrial myopathy, and subsequent mitochondrial DNA (mtDNA) analysis showed a deletion of approximately 5500 base pairs in 35 to 40% of her muscle mtDNA. We therefore conclude that this patient has developed the Kearns-Sayre syndrome after a Pearson syndrome-like crisis in her first year of life.